The Peasant Economy of Puno: 1820-1840: Repercussions of the military presence and textile production - Altamirano, Nelson (1991)
The interaction of military presence, peasant economy and scarcity of resources during the first twenty years of the Republic are facts that, in the existing bibliography on Puno, have always been associated. These works emphasize political instability and the succession of military actions in a context of economic crisis (Basadre, 1969, T.2), rather than the dynamics of the economic crisis. This is simply described as long (from the end of the 18th century until the emergence of the wool trade around 1840), and as basically mining and commercial (Choquehuanca, 1833; Jacobsen, 1983; Deustua, 1986; Tamayo, 1982:78).